A control theoretical approach to congestion control in packet networks - D. Cavendish; M. Gerla; S. Mascolo (IEEE/ACM Transactions on Networking, 2004)
In this paper, we introduce a control theoretical analysis of the closed-loop congestion control problem in packet networks. The control theoretical approach is used in a proportional rate controller, where packets are admitted into the network in accordance with network buffer occupancy. A Smith Predictor is used to deal with large propagation delays, common to high speed backbone networks. The analytical approach leads to accurate predictions regarding both transients as well as steady-state behavior of buffers and input rates. Moreover, it exposes tradeoffs regarding buffer dimensioning, packet loss, and throughput.
Keywords: Intelligent networks; Switches; Throughput; Quality of service; Transient analysis; Stability analysis; Communication system traffic control; Proportional control; Steady-state; Algorithm design and analysis